Economic Consequences of Housing Speculation - Gao, Zhenyu; Sockin, Michael; Xiong, Wei (Review of Financial Studies, 2020)
By exploiting variation in state capital gains taxation as an instrument, we analyze the economic consequences of housing speculation during the U.S. housing boom in the 2000s. We find that housing speculation, anchored, in part, on extrapolation of past housing price changes, led not only to greater price appreciation, economic expansions, and housing construction during the boom in 2004–2006 but also to more severe economic downturns during the subsequent bust in 2007–2009. Our analysis supports supply overhang and local household demand as two key channels for transmitting these adverse effects.